A qualitative evaluation of the implementation of a cultural competence project in rural Victoria - Olivia Mitchell; Lisa Bourke; Zubaidah Mohamed Shaburdin (Elsevier, 2021)
Abstract Objective: To explore the complex factors influencing the implementation of cultural competency frameworks for Aboriginal and Torres Strait Islander peoples within rural, Victorian, mainstream health and community service organisations. Methods: Semi‐structured telephone interviews were conducted with key individuals from 20 public health and community services in rural Victoria who had participated in the Koolin Balit Aboriginal Health Cultural Competence Project (KB‐AHCC project). Interviews were recorded and transcribed verbatim and a content analysis was undertaken. The findings informed the selection of six case study sites for more in‐depth analysis. Following this, an expert reference group provided feedback on the findings. Findings from the different data were triangulated to identify eight factors. Results: Key factors acting as barriers and/or enablers to implementing cultural competence frameworks were: comprehensive, structured tools; project workers; communication; organisational responsibility for implementation; prioritising organisational cultural competence resourcing; resistance to focussing on one group of people; and accountability. Conclusions: Embedding cultural competence frameworks within rural, mainstream health and community services requires sustained government resourcing, prioritisation and formal accountability structures. Implications for public health: Findings will inform and guide the future development, implementation and evaluation of organisational cultural competence projects for rural public health and community services.